Developing Fourth Wave Coffee Culture Towards Sustainable Gastronomy Tourism Growth in Riyadh - Maspul, Kurniawan Arif (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Riyadh, one of the cities with the most significant population in the Middle East, has become a tourist destination for gastronomy, apart from that with the development of the fourth-wave coffee culture. This is evidenced by the advancement of specialty coffee with the need for supermassive and sophisticated coffee roasteries and coffee shops to develop coffee communities of various age levels, apart from the global trend and also the development of local coffee acculturation without leaving the local wisdom heritage wealth of Saudi coffee as one of the global heritages. The remarkable growth of the fourth-wave coffee culture will also support sustainable development goals (SDGs) in the Middle East, making Riyadh a role model for the global coffee community, which is part of the coffee value chain constantly sustaining from the Jazan farm to the consumer cup. This research incorporates a qualitatively written with the instrument snowball approach through interview and observation and invites several stakeholders from coffee professionals who have been pioneers in the development of specialty coffee from product to community in the last decade in Riyadh. The impact of the findings through this research will assist in developing a coffee value chain in Saudi Arabia, which has helped strengthen local economic empowerment through SMEs and diversifying local wisdom from the global heritage of Saudi coffee. In addition, it is also assisted by a review of literature that explains the fourth-wave coffee culture, gastronomic tourism and sustainable development goals.